Analysis of intra-fraction prostate motion and derivation of duration-dependent margins for radiotherapy using real-time 4D ultrasound - Eric Pei Ping Pang; Kellie Knight; Qiao Fan; Sheena Xue Fei Tan; Khong Wei Ang; Zubin Master; Wing-Ho Mui; Ronnie Wing-Kin Leung; Marilyn Baird; Jeffrey Kit Loong Tuan (Physics and Imaging in Radiation Oncology, 2018)
Background and purpose: During radiotherapy, prostate motion changes over time. Quantifying and accounting for this motion is essential. This study aimed to assess intra-fraction prostate motion and derive duration-dependent planning margins for two treatment techniques. Material and methods: A four-dimension (4D) transperineal ultrasound Clarity® system was used to track prostate motion. We analysed 1913 fractions from 60 patients undergoing volumetric-modulated arc therapy (VMAT) to the prostate. The mean VMAT treatment duration was 3.4 min. Extended monitoring was conducted weekly to simulate motion during intensity-modulated radiation therapy (IMRT) treatment (an additional seven minutes). A motion-time trend analysis was conducted and the mean intra-fraction motion between VMAT and IMRT treatments compared. Duration-dependent margins were calculated and anisotropic margins for VMAT and IMRT treatments were derived. Results: There were statistically significant differences in the mean intra-fraction motion between VMAT and the simulated IMRT duration in the inferior (0.1 mm versus 0.3 mm) and posterior (−0.2 versus −0.4 mm) directions respectively (p ≪ 0.01). An intra-fraction motion trend inferiorly and posteriorly was observed. The recommended minimum anisotropic margins are 1.7 mm/2.7 mm (superior/inferior); 0.8 mm (left/right), 1.7 mm/2.9 mm (anterior/posterior) for VMAT treatments and 2.9 mm/4.3 mm (superior/inferior), 1.5 mm (left/right), 2.8 mm/4.8 mm (anterior/posterior) for IMRT treatments. Smaller anisotropic margins were required for VMAT compared to IMRT (differences ranging from 1.2 to 1.6 mm superiorly/inferiorly, 0.7 mm laterally and 1.1–1.9 mm anteriorly/posteriorly). Conclusions: VMAT treatment is preferred over IMRT as prostate motion increases with time. Larger margins should be employed in the inferior and posterior directions for both treatment durations. Duration-dependent margins should be applied in the presence of prolonged imaging and verification time. Keywords: Prostate, Intra-fraction movement, 4D Clarity ultrasound system, Real-time tracking, Margins